Concussion rates and effects on player performance in Major League Baseball players - Sabesan VJ; Prey B; Smith R; Lombardo DJ; Borroto WJ; Whaley JD (Dove Medical Press, 2018)
Vani J Sabesan,1 Beau Prey,2 Ryan Smith,3 Daniel J Lombardo,3 Wilfredo J Borroto,4 James D Whaley5 1Levitetz Department of Orthopaedic Surgery, Cleveland Clinic Florida, Weston, FL, USA; 2Western Michigan University School of Medicine, Kalamazoo, MI, USA; 3Department of Orthopaedic Surgery, Wayne State University School of Medicine, Detroit, MI, USA; 4Ponce School of Medicine and Health Sciences, Ponce, PR, USA; 5Beaumont Health System, Detroit, MI, USA Background: Major League Baseball (MLB) players are throwing the ball faster and hitting harder than ever before. Although some safety measures have been implemented, by decreasing the 15 days on the disabled list (DL) to the 7 days on the DL, concussion rates remain high across positions and may impact player performance. Our hypothesis was, there would be an increase in concussion incidence following implementation of the 7 day DL, but this would not have a negative impact on player’s postconcussion performance.Study design: This is a descriptive epidemiology study.Methods: The concussed players from 2005 to 2016 were identified from the MLB DL and verified using established new sources. Position-specific performance metrics from before and after injuries were gathered and compared to assess effects of the injury. Postconcussion performance metrics were compared before and after the 7-day DL rule implementation.Results: A total of 112 concussed players were placed on the DL. For all position players, the batting average (BA) and on-base percentage (OBP) showed a nonsignificant decline after injury (P=0.756). Although performance statistics for pitchers declined on average, the trend was not statistically significant. Postinjury BA and OBP did not significantly change before (0.355) and after (0.313) the 7-day DL rule change in 2011 (P=0.162).Conclusion: The incidence of reported concussion has increased with the 7-day DL rule change. Concussion incidence was highest in catchers and pitchers compared with all other players. The most common causes identified as being hit by pitch or struck by a foul ball or foul tip. While new league rules prevent collisions with catchers at home plate, injury by a foul tip was the most common cause for concussion. The shortened time spent on the DL did not negatively impact player’s performance. Further research on protective helmets for catchers may reduce concussion incidence. Keywords: baseball, epidemiology, head injuries/concussion, MLB, performance